Enhancing Young Children's Language Acquisition through Parent-Child Book-Sharing : A Randomized Trial in Rural Kenya - Knauer, Heather A.; Jakiela, Pamela; Ozier, Owen; Aboud, Frances; Fernald, Lia C.H. (World Bank, Washington, DC, 2019)
Worldwide, 250 million children under five (43 percent) are not meeting their developmental potential because they lack adequate nutrition and cognitive stimulation in early childhood. Several parent support programs have shown significant benefits for children's development, but the programs are often expensive and resource intensive. The objective of this study was to test several variants of a potentially scalable, cost-effective intervention to increase cognitive stimulation by parents and improve emergent literacy skills in children. The intervention was a modified dialogic reading training program that used culturally and linguistically appropriate books adapted for a low-literacy population. The study used a cluster randomized controlled trial with four intervention arms and one control arm in a sample of caregivers (n = 357) and their 24- to 83- month-old children ages 24 to 83 months (n = 510) in rural Kenya. The first treatment group received storybooks, while the other treatment arms received storybooks paired with varying quantities of modified dialogic reading training for parents. The main effects of each arm of the trial were examined, and tests of heterogeneity were conducted to examine differential effects among children of illiterate versus literate caregivers. Parent training paired with the provision of culturally appropriate children’s books increased reading frequency and improved the quality of caregiver-child reading interactions among preschool-age children. Treatments involving training improved storybook-specific expressive vocabulary. The children of illiterate caregivers benefited at least as much as the children of literate caregivers. For some outcomes, the effects were comparable; for other outcomes, there were differentially larger effects for children of illiterate caregivers.